Optical diagnostics on sooting laminar diffusion flames in microgravity - Will, Stefan; et al. (Microgravity Science and Technology, 2005)
Laser-induced incandescence was successfully applied to the investigation of soot formation in both buoyant and non-buoyant laminar jet diffusion flames. Microgravity experiments were conducted in the Drop Tower Bremen, Germany. By the use of imaging laser-induced incandescence (LII) it was possible for the first time to obtain simultaneously two-dimensional information on soot concentration and primary particle size under microgravity. Additionally, temperature fields were measured by 2-color emission pyrometry. Results for the fuels propane and ethene show that soot formation and oxidation is drastically altered under microgravity. Maximum temperatures are reduced by roughly 220 K and 120 K, respectively, which in the case of ethene results in a termination of oxidation processes and the emission of soot. The distribution of soot within the non-buoyant flames is always concentrated in relatively small bands. For all non-buoyant flames investigated the maximum primary particle size roughly doubles compared to the buoyant ones. © Z-Tec Publishing, Bremen.